Az önreflexió megváltozott tartalma online oktatás idején a vallástanárok nézőpontjából - Gabriella GORBAI (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2022)
The Changed Content of Self-Reflection during Online Teaching – The Perspective of Religion Teachers.The spread of the coronavirus pandemic took its toll on all areas of life, and we can safely say that it has fundamentally altered education, too, throughout the globe. Teachers around the world exhibited a wide array of responses to the changed situation, some of them having no real problem with the transition to online teaching, while the majority of them having suffered a considerable loss of faith concerning their effectiveness as teachers when coming up against the changed environment and the new challenges. Most teachers of religion were experiencing a sense of lack due to the enforced suspension of the day-to-day interpersonal relationships, considering that personal encounters have a particular relevance to religion as a subject on ac-count of its pastoral care and spiritual aspects. Teachers did not only have to struggle with the new challenges emerging in their working environment, with problems around ensuring an appropriate technological background, or with the transformation of the existent teaching material for online use, but the adoption of a successful coping in a situation never dealt with before could be affected by certain (psychological) factors running much deeper such as their faith/beliefs, while the reasons for coming to a deadlock can often be traced back to the issues of professional identity, (sense of) mission, or religious spirituality. The present study points out that (self-)reflection increases teachers’ efficiency and productiveness, and it is the author’s belief that conscious reflection can seriously add to teachers’ professional fulfilment during the crisis situation created by the virus, when online teaching methods have to be adopted, since re-flection can put intrinsic motivation to work, as a result of which teachers can set a course to their own development. Further, we will present a reflection model that provides a content framework for reflection and wherein there is a possibility for a deeper-level reflection as well, thus going beyond the aspects of environment, behaviour, and views and reaching the levels of professional identity, mission, and religious spirituality.